Single-cell analysis links DCUN1D5 to immune remodeling and cisplatin resistance in recurrent osteosarcoma - Xin Wu; Woding Deng; Qiangqiang Zhao; Jianbin Xiong (Communications Biology)
Abstract Cisplatin is the primary chemotherapeutic agent for osteosarcoma. However, a significant proportion of patients develop resistance post-treatment, leading to disease recurrence and presenting profound clinical challenges. To understand the mechanisms underlying osteosarcoma recurrence and cisplatin resistance, particularly from the tumor microenvironment perspective, we consolidated numerous single-cell RNA sequencing datasets, offering an encompassing insight into the osteosarcoma microenvironment. When juxtaposing scRNA-seq with bulk RNA-seq data, we observed a strong correlation between high DCUN1D5 expression in osteosarcoma and patient survival. This gene amplifies osteosarcoma’s anti-apoptotic, invasive, stem-cell-like traits and PI3K/AKT/GSK3β pathway phosphorylation and fosters cisplatin resistance. Subsequent research revealed that cisplatin-resistant osteosarcoma cells excrete DCUN1D5-rich exosomes, facilitating the maturation of osteoclast precursors. Excessive osteoclast activity is a pivotal contributor to osteosarcoma recurrence and resistance. Given these insights, DCUN1D5 is a promising therapeutic target for osteosarcoma recurrence and drug resistance.